A circle of ashes - Tiernan, Cate (Tiernan, Cate. Balefire, 2005)
While Daedalus schemes to use the coven's power for his own dark purposes, seventeen-year-old twins Clio and Thais seek to learn who is trying to hurt them and, in the process, discover that Thais's magick has explosive power.